Предмет: Алгебра,
автор: valeria010
log по основанию 3 (6-3x) + log по основанию 3 (1-x) = log по основанию 3 36
Ответы
Автор ответа:
0
log3(6-3x) + log3(1-x) = log3(36)
log3((6-3x)(1-x))=log3(36)
(6-3x)(1-x)=36
6-6x-3x+3x^2=36
3x^2-9x-30=0
x^2-3x-10=0
x=5; x=-2
ОДЗ: 6-3x>0; 3x<6; x<2
1-x>0; x<1 => x < 1
Ответ: -2
Похожие вопросы
Предмет: Русский язык,
автор: dahanova78
Предмет: Алгебра,
автор: munisamrtv
Предмет: География,
автор: OJlElllKA
Предмет: Литература,
автор: KrisTV
Предмет: Алгебра,
автор: chursina